(3GdeNJUQ aj eSFhdjI GdegfOS hGdebGhd aj YbhO GdJTjjOs - (3fHjd YHOGdHOjY jMjis (2023)
(3jYQV gPG GdcJGH ddeYdheGJ GdCSGSjI GdJj dG Zfi YfgG ddegfOS GdPj jHZi GdYed aj EOGQI YbhO eTQhYGJ GdJTjjO(B. (3ajHOC HGdJYQja HeHGOF heUGOQ GdbGfhf, Ke JWHjb GdbGfhf hGdCgdjI GddGReI dUMI GdJUQa GdbGfhfj hcPdc YhGQVgG hehGbYgG, Ke GdJYQja HeUGOQ GdEdJRGe aj GdMbhb GdYjfjI hGdTNUjI, Ke GdYbO hGdeSFhdjI GdYbOjI Ke CWQGa GdYbO hCQcGfg heGgjI GdhYO HGdJYGbO hNWGH GdfhGjG Ke dHWdGf GdYbO hOQLGJg, hELGRJg hJaSjQg hJfajPg Ke bjGe GdeSFhdjI GdYbOjI hcjajI GdOaY HYOe GdJfajP, Ke GdZQGeI GdJgOjOjI hGdTQW GdLRGFj aj GdYbOjf GdeOfj hGdEOGQj, Ke GdJYhjV hGdahGFO hCfhGYgG hTQhW GSJMbGbgG, Ke MGdGJ EfgGA GdYbO aj cd ef GdYbO GdeOfi hGdYbO GdEOGQj Ke jYQV GdcJGH Edi GdeUGOQ ZjQ GdEQGOjI ddEdJRGe (B) (3GdhGbYI GdeGOjI (B( (3HfhYjgG GdChd GdaYd GdVGQ (B( (3GdeSFhdjI GdJbUjQjI HCQcGfgG hCfhGYgG (B( (3hCfhGY GdVQQ hGdJYhjV Yfg Ke CfhGY GdeSFhdjI GdJbUjQjI GdeSFhdjI Yf GdaYd GdTNUj hYf aYd GdZjQ hYf aYd GdTjF Ke GdKGfj hgh GdeSFhdjI Yf GdaYd GdfGaY(B. (3Ke jJfGhd GdcJGH CfhGY GdYbhO GdgfOSjI hjNU HGdOQGSI YbO GdebGhdI hbhGYO JMOjO hJZjjQ GdCLQ ajgG dJMbjb GdJhGRf GdYbOj ddYbOjf GdeOfi hGdEOGQi, Ke BKGQ YbO GdEfTGAGJ hGdJRGeGJ cd ef GdeGdc hGdebGhd, hMGdGJ EfbVGA YbO GdebGhdI Ke YbO GdebGhdI ef GdHGWf hGdYdGbI Hjf CWQGag hGdeGdc, Ke eSJfOGJ YbO GdEfTGAGJ hChdhjJgG hjfGbT hVY GdLOhd GdRefj ef hKGFb GdYbO(B. (3hjYQV cPdc dYbO GdeThQI GdgfOSjI hMGdGJ JZjQ GdCLQ aj YbO GdebGhdI Ke YbO JSdje eaJGM hYbhO JfajP GdHfjI GdCSGSjI Ke jYQV dbhGYO GdJYGbO eY GdLgGJ GdEOGQjI Yf WQjb GdefGbUI Ch GdeRGjOI, hcPdc jfGbT eNGWQ QH GdYed hGdebGhd aj JMOjO Kef GdYbO aj YbhO GdEfTGAGJ hjfGbT GdcJGH HGSJaGVI CcHQ eSFhdjI GdeTjOjf aj VhA fUhU GdbGfhf GdNGUI HeG jSei GdVeGf GdeYeGQj HYO HjGf NUGFUg hJYdbg HGdfXGe GdYGe, hGdGNJdGa aj WHjYI GdYdGbI GdJYGbOjI Hjf QH GdYed hGdebGhd bHd JSdje GdeHfi EHJOGFjG hHYOg hGdENJdGa Hjf GdJSdje aj GdJYQja GdgfOSj hGdJYQja GdbGfhfj(B. (3hjYQV GdcJGH ebOeI eNJUQI dbGfhf GdYed GdaQOi, hdbGfhf GdEKHGJ, hCNjQG jJYQV GdcJGH HTjA ef GdJaUjd dhSGFd Md GdfRGY aj YbhO GdJTjjO hHGdCNU WQjb GdJMcje aj GdbGfhf GdeUQi heLdS aV GdfRGY aj YbO GdajOjc(B.s
Keywords: (3GdYbhO GdgfOSjIs; (3YbhO GdEfTGAGJ s; (3GdebGhds